Generator governing system based on grey prediction and extension control. Issue 15 (27th September 2017) - Wang, Mingdong; Wang, Xueke; Su, Xiangjing; Li, Xiangyang; Yang, Yihang
Abstract : To improve the performance of the governing system as well as the stability of the power system, the authors propose grey prediction extension control (GPEC) in the design of generator governing system. Comparing with the conventional control strategy such as conventional proportional–integral–derivative control and simple extension control, GPEC is more suitable for the complex, huge‐dimension and time‐varying modern power systems. Both a simple hydropower system and a typical multi‐machine system are studied, respectively. The simulation results indicate that the proposed GPEC governor controller performs better in reducing overshoot and adjusting time with superiority in leading the system into a stable state.